Comparison of Two Cyberknife Planning Approaches for Multiple Brain Metastases - Ji, Tianlong; Song, Yaowen; Zhao, Xinyu; Wang, Yuzi; Li, Guang (Frontiers in Oncology, 2022)
Purpose To compare the delivery efficiency, plan quality, and PTV and normal brain dosimetry between different Cyberknife planning approaches for multiple brain metastases (MBM), and to evaluate the effects of the number of collimators on the related parameters. Methods The study included 18 cases of MBM. The cyberknife treatment plans were classified as Separate or Combined. For the Separate plan, each lesion was targeted by the collimator auto-selection method (Conformality 2/3 collimators). For the Combined plan, a PTV including all PTVs was targeted by the collimators. Monitor units (MUs), number of nodes and beams, estimated fraction treatment time (EFTT), new conformity index (nCI), dose gradient index (GI), homogeneity index (HI), PTV minimum/maximum dose (Dmax/Dmin), volume doses (D2% and D98%), maximum doses to lenses, optic nerves, and brainstem as well as normal brain 3, 6, 10, and 12 Gy (V3Gy-V12Gy) were compared. Results Compared to the Combined plan, the Separate plan had fewer nodes and beams, shorter EFTT, smaller PTV Dmin, normal brain dose, and GI, and larger HI. The Separate plan with 2 collimators also had worse PTV coverage. In the Combined plan, more collimators increased beams, EFTT, GI, and normal brain dose, but improved the PTV Dmin. Among treatments based on the Separate approach, there were obvious differences between plans for most of the items except the nCI. Fewer collimators resulted in significantly reduced beams, EFTT, PTV D98%, and normal brain dose with improved GI, although PTV Dmin and MUs were decreased while HI was increased. Conclusion Both approaches met the requirements for SRS/HFSRT. We found that Separate plans improved treatment efficiency and normal tissue dosimetry.